Effects of PSA Removal from NCAM on the Critical Period Plasticity Triggered by the Antidepressant Fluoxetine in the Visual Cortex - Guirado, Ramon; La Terra, Danilo; Bourguignon, Mathieu; Carceller, Hector; Umemori, Juzoh; Sipilä, Pia; Nacher, Juan; Castrén, Eero (Frontiers in Cellular Neuroscience, 2016)
Neuronal plasticity peaks during critical periods of postnatal development and is reduced towards adulthood. Recent data suggests that windows of juvenile-like plasticity can be triggered in the adult brain by antidepressant drugs such as Fluoxetine. Although the exact mechanisms of how Fluoxetine promotes such plasticity remains unknown, several studies indicate that inhibitory circuits play an important role. The polysialylated form of the neural cell adhesion molecules (PSA-NCAM) has been suggested to mediate the effects of Fluoxetine and it is expressed in the adult brain by mature interneurons. Moreover, the enzymatic removal of PSA by neuroaminidase-N not only affects the structure of interneurons but also has been shown to play a role in the onset of critical periods during development. We have here used ocular dominance plasticity in the mouse visual cortex as a model to investigate whether removal of PSA might influence the Fluoxetine-induced plasticity. We demonstrate that PSA removal in the adult visual cortex alters neither the baseline ocular dominance, nor the fluoxetine-induced shift in the ocular dominance. We also show that both chronic Fluoxetine treatment and PSA removal independently increase the basal FosB expression in parvalbumin (PV) interneurons in the primary visual cortex. Therefore, our data suggest that although PSA-NCAM regulates inhibitory circuitry, it is not required for the reactivation of juvenile-like plasticity triggered by Fluoxetine.